Reading leila aboulela's minaret 2005 as an islamic feminist novel: nejwa 's empowerment through spirituality and social connection - Ben ammar,Amel; Boumous,B (Faculty of Letters and Foreign Languages Department of English, 2017)
Reading leila aboulela's minaret 2005 as an islamic feminist novel: nejwa 's empowerment through spirituality and social connection